Stainless Steel Passivation Using Electropolishing and Thermal Treatments. (3rd April 2017) - Korinko, Paul; Wyrwas, Richard; Spencer, William; Peters, Brent; Stein, Edward; Hitchcock, Dale
Abstract: Tritium is highly reactive with many materials. It is adsorbed onto and absorbed through the surface of containment vessels subsequently modifying the contained gas composition by isotopic exchange and catalytic reactions with surface elements and adsorbed gas species. Savannah River Tritium Enterprise (SRTE) uses a proprietary surface treatment that is intended to render the surface inert. Unfortunately, this process has not proven to be sufficiently robust for containing tritium gas standards. SRTE has funded a project that will explore the effects of electropolishing and vacuum and oxidizing thermal treatments on surface passivation of stainless steel (SS). Herein, a statistically designed series of experiments will be discussed that will inform optimized parameters for acid composition, current density, and other electrochemical process variables for the passivation of SS. The surfaces were analyzed using Laser Induced Breakdown Spectroscopy (LIBS), Auger Electron Spectroscopy (AES), Atomic Force Microscopy (AFM), and Scanning Electron Microscopy (SEM). Novel techniques to characterize the passive layers are also being developed. In future experiments, gas sample bottles will be loaded with protium and deuterium to determine the relative exchange characteristics of the treated vessels. Previous work has indicated that if little protium ingrowth occurs or few contaminant species form, e.g., methane or ammonia, and little hydrogen exchange occurs in a protium and deuterium gas mixture the treatment is suitable for maintaining the tritium stability. This statement is not intended to imply that tritium, deuterium, protium mixes will not exchange, only that these results are useful as a screening tool prior to tritium exposure.